Coated water electrolysis catalyst as well as preparation method and application thereof

By using Ru-MnO2 as the matrix and Ir atom as the reactive site in the electrolytic water catalyst, the problem of high cost of hydrogen production by electrolytic water is solved, and efficient utilization of precious metals and improved electrolytic efficiency is achieved.

CN119506970APending Publication Date: 2025-02-25HUAYI NEW ENERGY MATERIALS (SHANGHAI) CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411671536.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-21
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The cost of producing hydrogen OER by electrolyzing water is too high, mainly due to the high content of precious metal Ir and the durability of the ruthenium oxide catalyst.

Method used

Through the multi-layer coating preparation process, Ru-MnO2 is used as the matrix, and the Ir atoms are exposed to the catalyst surface, which increases the atomic utilization rate of Ir and reduces the amount of Ir, while reducing the electrochemical oxygen evolution reaction potential through the synergistic action of Ru.

Benefits of technology

It effectively improves the utilization rate and electrochemical activity area of ​​precious metals, reduces the OER side cost of electrolytic water catalysts, and improves the electrolytic efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119506970A_ABST
    Figure CN119506970A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of proton exchange membrane electrolyzed water, and particularly relates to a coated electrolyzed water catalyst as well as a preparation method and application thereof. The catalyst takes Ru-Mn02 as a carrier, and iridium is coated on the surface of the carrier. According to the water electrolysis catalyst, an existing bimetal Ir-based supporting process is improved, the utilization rate of precious metal of bimetal Ir and Ru after improvement is effectively increased, and the electrochemical area is further increased.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of proton exchange membrane water electrolysis, and specifically relates to a coated water electrolysis catalyst and a preparation method and application thereof. Background Art

[0002] In order to better achieve the "dual carbon" goal, the transformation of new energy is imminent. Among the many new energy sources, hydrogen energy is environmentally friendly because its only product after combustion is water, and it has great development and application potential. Common methods of hydrogen production include fossil energy hydrogen production, industrial by-product hydrogen production, and water electrolysis hydrogen production. Among them, water electrolysis can couple renewable energy such as light energy, wind and tidal energy, and waste electricity, which can reduce energy waste and achieve efficient energy utilization.

[0003] Hydrogen production by water electrolysis is an energy conversion technology that separates the hydrogen and oxygen elements in water molecules and forms corresponding single molecules. As the core part of water electrolysis technology, the electrochemical oxygen evolution reaction (OER) is a key step in determining the electrolysis rate. Over the past few decades, OER catalysts have developed into precious metal Ir and Ru oxides as the main water electrolysis catalysts. Iridium oxide is the most commercially mature water electrolysis catalyst, but its high price and reserves are the key obstacles to the further marketization of water electrolysis technology. Ruthenium oxide catalysts have the potential to replace iridium oxide, but their durability issues remain unsolved.

[0004] Reducing the content of Ir and increasing the amount of Ru is the mainstream trend in the development of commercial water electrolysis catalysts. Increasing the electrochemical active area and atomic utilization of Ir catalysts is an important way to reduce the amount of Ir. Summary of the invention

[0005] In order to solve the problem of high cost of hydrogen production (OER) by electrolysis of water, the present invention improves the existing bimetallic Ir-based loading process. After the improvement, the utilization rate of the precious metals of bimetallic Ir and Ru is effectively improved, and the electrochemical area is further increased.

[0006] The present invention uses a multi-layer coating preparation process to expose Ir atoms serving as reaction active sites on the catalyst surface, while the matrix serving as a structural support is Ru-MnO2.

[0007] Through the design of the preparation process, a higher atomic utilization rate of Ir is achieved; at the same time, the synergistic effect of Ru atoms can effectively reduce the potential of the electrochemical oxygen evolution reaction and improve the electrolysis efficiency; due to the full alloying of the matrix structure, sufficient mechanical stability of the catalyst is guaranteed.

[0008] In order to achieve the above object, the first aspect of the present invention discloses a method for preparing a water electrolysis catalyst, comprising the following steps:

[0009] (1) Matrix alloy precursor: RuCl 3 Hydrate and MnCl 2 The hydrate is dissolved in deionized water as a precursor and mixed to obtain a solution;

[0010] (2) Dispersion and drying: Add carbon black, ethanol and deionized water to the solution. After ultrasonic dispersion, transfer to a magnetic stirrer to dry the solvent and collect the powder.

[0011] (3) High-temperature reduction: The collected powder is placed in a muffle furnace and reduced under an inert atmosphere;

[0012] (4) Low-temperature oxidation / decarbonization: After the reduction is completed, the temperature is lowered to 450°C for oxidation treatment, and the atmosphere is changed to air. The oxidation time is 8 hours;

[0013] (5) Refining: Use a mechanical crusher to refine the catalyst;

[0014] (6) Pickling: The crushed powder is placed in an acidic environment with a pH of 0.7 to 1.5 for 8 to 12 hours, followed by washing and filtering. The transition metal ions Mn on the surface of the matrix are washed away by pickling, allowing the transition metal ions to fill the interior of the matrix, reducing the use of the precious metal Ru, providing stronger structural support, and improving the mechanical stability of the alloy.

[0015] (7) Addition of iridium salt: 3 The hydrate is dissolved in a 1 mol / L hydrochloric acid and ethanol mixed solution, and after ultrasonic dispersion for half an hour, it is transferred to a constant temperature magnetic stirrer with the powder after acid washing in step (6), and an appropriate amount of sodium borohydride is added to the mixed solution to react for 1 hour. After washing and drying the mixture, the remaining powder is collected. The molar ratio of iridium to ruthenium cations is 1:1-3; through the improvement of the specific process, the matrix is ​​first prepared, and then the ion molar ratio between the noble metal elements is adjusted so that the Ir atoms serving as the reaction active sites are exposed on the catalyst surface.

[0016] (8) High temperature reduction: placing the powder collected in step (7) in a muffle furnace and reducing it under an inert atmosphere;

[0017] (9) Low temperature oxidation: After the reduction is completed, the temperature is about 300-500°C for oxidation treatment, and the atmosphere is changed to compressed air. The oxidation time is 3-5 hours;

[0018] (10) Catalyst acquisition: Through filtering, washing and drying steps, a water electrolysis catalyst with low Ir loading and high noble metal specific surface area is obtained.

[0019] In some embodiments, step (1) RuCl 3 Hydrate and MnCl2 In the hydrate, the molar ratio of Ru and Mn ions is 1:1-3.

[0020] In some embodiments, the ratio of ethanol to water in step (2) is 1:1; the molar ratio of carbon black to metal ions is 1:3, and the carbon black is one of Cabot or Ketjen black.

[0021] In some embodiments, in step (2) and step (7), the drying conditions of the magnetic stirrer are: a rotation speed of 600 r / s at 80°C.

[0022] In some embodiments, in step (3), the reduction is carried out at 800° C. and the inert atmosphere is H 2 (5%)-Ar(95%), the reduction time is 2-5h, and the heating and cooling rate is maintained at 2-5℃ / min.

[0023] In some embodiments, in step (6), hydrochloric acid is preferably used to adjust the pH value, and the pickling time is 10 hours.

[0024] In some embodiments, in step (8), the reduction conditions are 900°C, the inert atmosphere is H2(5%)-Ar(95%), the reduction time is 2-5h, and the heating and cooling rate is maintained at 2-5°C / min.

[0025] The second aspect of the present invention discloses a water electrolysis catalyst, which is prepared by the above-mentioned preparation method, wherein the water electrolysis catalyst comprises a substrate and Ir atoms attached to the surface of the substrate;

[0026] The matrix includes Ru-Mn. 2 .

[0027] In some embodiments, the electrolytic water catalyst structure is divided into three layers: inner, middle, and outer;

[0028] The metal elements in the inner layer of the catalyst include Ru and Mn elements, the metal elements in the middle layer include Ir and Ru elements, and the metal elements in the outer layer include Ir elements.

[0029] The third aspect of the present invention discloses the use of the above-mentioned water electrolysis catalyst in electrocatalytic water electrolysis in an electrochemical oxygen evolution reaction.

[0030] Compared with the prior art, the present invention has the following beneficial effects:

[0031] The present invention Ru-MnO 2 As a supporting matrix for precious metals Ir and Ru, Ru-MnO 2It has good electrical conductivity. Mn doping is beneficial to reduce the amount of Ru metal. The bimetallic Ir and Ru improve the activity and durability of the catalyst. The liquid phase reduction method is adopted, and the reducing agent sodium borohydride is introduced at a certain stirring speed, so that the precious metal Ir can be in the Ru-MnO 2 At the same time, sodium borohydride can inhibit the oxidation of Ir and maintain a certain proportion of metallic Ir, which is beneficial to the improvement of electrochemical activity and durability; more importantly, the use of Ru-MnO 2 The loading process reduces the amount of Ir used and the cost of the OER end of the catalyst. At the same time, the synergistic effect of Ru further improves the electrolysis efficiency. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 Schematic diagram of the structure of the water electrolysis catalyst. DETAILED DESCRIPTION

[0033] The technical scheme of the present invention is described in detail below in conjunction with the accompanying drawings and embodiments, but the present invention is not limited to the scope of the embodiments. The process parameters not specified in the embodiments of the present application can be carried out according to conventional methods, and the raw materials used can be obtained through commercial channels.

[0034] Example 1

[0035] A method for preparing an OER water electrolysis catalyst comprises the following steps:

[0036] (1) Material weighing: weigh carbon black and RuCl in a molar ratio of 1:3:3. 3 Hydrate and MnCl 2 Hydrate.

[0037] (2) Precursor dispersion: RuCl 3 Hydrate and MnCl 2 The hydrate precursor was dissolved in deionized water and dispersed by ultrasound. Then, appropriate amounts of carbon black, ethanol and deionized water (the ratio of alcohol to water was 1:1) were added to the solution. After half an hour of ultrasonic dispersion, the solution was transferred to a magnetic stirrer, and the solvent was dried at 80°C and 600 r / s, and the remaining powder was collected.

[0038] (3) High-temperature reduction: The collected powder was placed in a muffle furnace at 800 °C and H 2 The reduction was carried out in a (5%)-Ar (95%) atmosphere for 5 h, and the heating and cooling rate was maintained at 5°C / min.

[0039] (4) Low-temperature oxidation / decarbonization: After the reduction is completed, the temperature is lowered to 450°C for oxidation treatment, and the atmosphere is changed to air. The oxidation time is 8 hours.

[0040] (5) Refinement: Use a mechanical crusher to refine the catalyst.

[0041] (6) Acid washing: The crushed powder is placed in a 0.1 mol / L hydrochloric acid solution and acid washed for 10 h, followed by washing and filtering.

[0042] (7) Add iridium salt: weigh IrCl 3 The hydrate is dissolved in a 1 mol / L mixed solution of hydrochloric acid and ethanol, and after ultrasonic dispersion for half an hour, it is transferred to a constant temperature magnetic stirrer with the powder after acid washing in step (6), and an appropriate amount of sodium borohydride is added to the mixed solution to react for 1 hour. After washing and drying the mixture, the remaining powder is collected. The molar ratio of iridium to ruthenium cations is 1:1-3.

[0043] (8) High-temperature reduction: The collected powder was placed in a muffle furnace and reduced at 900°C in a H2 (5%)-Ar (95%) atmosphere for 5 h. The heating and cooling rate was maintained at 5°C / min.

[0044] (9) Low-temperature oxidation: After the reduction is completed, the temperature is reduced to 350°C for oxidation treatment, and the atmosphere is changed to compressed air. The oxidation time is 5 hours.

[0045] (10) Catalyst acquisition: A high specific surface area water electrolysis catalyst with low Ir loading is obtained through filtering, washing and drying.

[0046] Example 2

[0047] A method for preparing an OER water electrolysis catalyst comprises the following steps:

[0048] (1) Material weighing: weigh carbon black and RuCl in a molar ratio of 1:3:3. 3 Hydrate and MnCl 2 Hydrate.

[0049] (2) Precursor dispersion: RuCl 3 Hydrate and MnCl 2 The hydrate precursor was dissolved in deionized water and dispersed by ultrasound. Then, appropriate amounts of carbon black, ethanol and deionized water (the ratio of alcohol to water was 1:1) were added to the solution. After half an hour of ultrasonic dispersion, the solution was transferred to a magnetic stirrer, and the solvent was dried at 80°C and 600 r / s, and the remaining powder was collected.

[0050] (3) High-temperature reduction: The collected powder was placed in a muffle furnace at 800 °C and H 2 The reduction was carried out in a (5%)-Ar (95%) atmosphere for 5 h, and the heating and cooling rate was maintained at 5°C / min.

[0051] (4) Low-temperature oxidation / decarbonization: After the reduction is completed, the temperature is lowered to 450°C for oxidation treatment, and the atmosphere is changed to air. The oxidation time is 8 hours.

[0052] (5) Refinement: Use a mechanical crusher to refine the catalyst.

[0053] (6) Acid washing: The crushed powder is placed in a 0.1 mol / L hydrochloric acid solution and acid washed for 10 h, followed by washing and filtering.

[0054] (7) Addition of iridium salt: Dissolve the weighed IrCl3·hydrate in a 1 mol / L mixed solution of hydrochloric acid and ethanol, and transfer the mixture to a constant temperature magnetic stirrer with the powder after acid washing in step (6) after ultrasonic dispersion for half an hour, and add an appropriate amount of sodium borohydride to the mixed solution to react for 1 hour. After washing and drying the mixture, collect the remaining powder. The molar ratio of iridium to ruthenium cation is 1:1-3.

[0055] (8) High-temperature reduction: The collected powder was placed in a muffle furnace and reduced at 900°C in a H2 (5%)-Ar (95%) atmosphere for 5 h. The heating and cooling rate was maintained at 5°C / min.

[0056] (9) Low-temperature oxidation: After the reduction is completed, the temperature is reduced to 350°C for oxidation treatment, and the atmosphere is changed to compressed air. The oxidation time is 5 hours.

[0057] (10) Catalyst acquisition: A high specific surface area water electrolysis catalyst with low Ir loading is obtained through filtering, washing and drying.

[0058] Example 3

[0059] A method for preparing an OER water electrolysis catalyst comprises the following steps:

[0060] (1) Material weighing: weigh carbon black and RuCl in a molar ratio of 1:3:6. 3 Hydrate and MnCl 2 Hydrate.

[0061] (2) Precursor dispersion: RuCl 3 Hydrate and MnCl 2 The hydrate precursor was dissolved in deionized water and dispersed by ultrasound. Then, appropriate amounts of carbon black, ethanol and deionized water (the ratio of alcohol to water was 1:1) were added to the solution. After half an hour of ultrasonic dispersion, the solution was transferred to a magnetic stirrer, and the solvent was dried at 80°C and 600 r / s, and the remaining powder was collected.

[0062] (3) High-temperature reduction: The collected powder was placed in a muffle furnace at 800 °C and H2 The reduction was carried out in a (5%)-Ar (95%) atmosphere for 5 h, and the heating and cooling rate was maintained at 5°C / min.

[0063] (4) Low-temperature oxidation / decarbonization: After the reduction is completed, the temperature is lowered to 450°C for oxidation treatment, and the atmosphere is changed to air. The oxidation time is 8 hours.

[0064] (5) Refinement: Use a mechanical crusher to refine the catalyst.

[0065] (6) Acid washing: The crushed powder is placed in a 0.1 mol / L hydrochloric acid solution and acid washed for 10 h, followed by washing and filtering.

[0066] (7) Ir salt dispersion: Weigh IrCl in a molar ratio of 1:3 to Ru atoms. 3 The hydrate was dissolved in 500 ml of deionized water, and the washed and filtered solid was added to the solution. After ultrasonic dispersion for half an hour, it was transferred to a magnetic stirrer.

[0067] (8) High-temperature reduction: The collected powder was placed in a muffle furnace and reduced at 900°C in a H2 (5%)-Ar (95%) atmosphere for 5 h. The heating and cooling rate was maintained at 5°C / min.

[0068] (9) Low-temperature oxidation: After the reduction is completed, the temperature is reduced to 350°C for oxidation treatment, and the atmosphere is changed to compressed air. The oxidation time is 5 hours.

[0069] (10) Catalyst acquisition: A high specific surface area water electrolysis catalyst with low Ir loading is obtained through filtering, washing and drying.

[0070] Comparative Example 1

[0071] (1) Precursor dispersion: weigh carbon black, IrCl and 3 Hydrate and RuCl 3 The hydrate was dissolved in a 1 mol / L mixed solution of hydrochloric acid and ethanol, and after ultrasonic dispersion for half an hour, it was transferred to a magnetic stirrer, and the solvent was dried at 80°C and 600 r / s, and the remaining powder was collected.

[0072] (2) High-temperature reduction: The collected powder was placed in a muffle furnace at 900 °C and H 2 The reduction was carried out in a (5%)-Ar (95%) atmosphere for 5 h, and the heating and cooling rate was maintained at 5°C / min.

[0073] (3) Low-temperature oxidation: After the reduction is completed, the temperature is reduced to 350°C for oxidation treatment, and the atmosphere is changed to compressed air. The oxidation time is 5 hours.

[0074] Comparative Example 2

[0075] (1) Precursor dispersion: weigh IrCl 3 Hydrate and RuCl 3 The hydrate was dissolved in a 1 mol / L mixed solution of hydrochloric acid and ethanol, and after ultrasonic dispersion for half an hour, it was transferred to a magnetic stirrer, and the solvent was dried at 80°C and 600 r / s, and the remaining powder was collected.

[0076] (2) High-temperature reduction: The collected powder was placed in a muffle furnace at 900 °C and H 2 The reduction was carried out in a (5%)-Ar (95%) atmosphere for 5 h, and the heating and cooling rate was maintained at 5°C / min.

[0077] (3) Low-temperature oxidation: After the reduction is completed, the temperature is reduced to 350°C for oxidation treatment, and the atmosphere is changed to compressed air. The oxidation time is 5 hours.

[0078] Comparative Example 3

[0079] (1) Precursor dispersion: weigh carbon black, IrCl and 3 Hydrate, RuCl 3 Hydrate and MnCl 2 The hydrate was dissolved in a 1 mol / L mixed solution of hydrochloric acid and ethanol, and after ultrasonic dispersion for half an hour, it was transferred to a magnetic stirrer, and the solvent was dried at 80°C and 600 r / s, and the remaining powder was collected.

[0080] (2) High-temperature reduction: The collected powder was placed in a muffle furnace at 900 °C and H 2 The reduction was carried out in a (5%)-Ar (95%) atmosphere for 5 h, and the heating and cooling rate was maintained at 5°C / min.

[0081] (3) Low-temperature oxidation: After the reduction is completed, the temperature is reduced to 350°C for oxidation treatment, and the atmosphere is changed to compressed air. The oxidation time is 5 hours.

[0082] The catalytic activity of the catalysts prepared in Examples 1-3 and Comparative Examples 1-3 was evaluated by measuring the specific surface area, overpotential (1.23 V higher, i.e., higher than the voltage required for theoretical electrolysis), Tafel slope (mV dec) obtained by LSV fitting, and the relative humidity. -1 ) and the electrochemically active specific surface area (ECSAcm 2 / mg); the test conditions were room temperature in sulfuric acid (C = 0.5 mol / L), the counter electrode was pt, and the reference electrode was Hg / Hg 2S04, the scan rate is 10 mv / s, and the 5th scan of the voltammetric curve is taken.

[0083] Four parameters are used to verify the electrochemical activity of the catalyst: BET; overpotential; Tafel slope; ECSA.

[0084]

[0085]

[0086] The present invention is not limited to the above-mentioned embodiments. Any changes in shape or structure shall fall within the protection scope of the present invention. The protection scope of the present invention is defined by the attached claims. Those skilled in the art may make various changes, modifications, substitutions, combinations and simplifications to these embodiments without departing from the principle and essence of the present invention. All of these shall be equivalent replacement methods and fall within the protection scope of the present invention.

Claims

1. A method for preparing a water electrolysis catalyst, characterized in that: The steps include: (1) Matrix alloy precursor: RuCl3·hydrate and MnCl2·hydrate are dissolved in deionized water as precursors to obtain a solution; (2) Dispersion and drying: Add carbon black, ethanol and deionized water to the solution. After ultrasonic dispersion, transfer to a magnetic stirrer to dry the solvent and collect the powder. (3) High-temperature reduction: The collected powder is placed in a muffle furnace and reduced under an inert atmosphere; (4) Low-temperature oxidation / decarbonization: After the reduction is completed, the temperature is lowered to 450°C for oxidation treatment, and the atmosphere is changed to air. The oxidation time is 8 hours; (5) Refining: Use a mechanical crusher to refine the catalyst; (6) Acid washing: The crushed powder is placed in an acidic environment with a pH of 0.7 to 1.5 for 8 to 12 hours, followed by washing and filtering; (7) Addition of iridium salt: Dissolve the weighed IrCl3·hydrate in a 1 mol / L mixed solution of hydrochloric acid and ethanol, and transfer the mixture to a constant temperature magnetic stirrer with the powder after acid washing in step (6) after ultrasonic dispersion for half an hour, and add sodium borohydride to the mixed solution to react for 1 hour. Wash and dry the mixture, and collect the remaining powder, wherein the molar ratio of iridium to ruthenium cations is 1:1-3; (8) High temperature reduction: placing the powder collected in step (7) in a muffle furnace and reducing it under an inert atmosphere; (9) Low temperature oxidation: After the reduction is completed, the temperature is about 300-500°C for oxidation treatment, and the atmosphere is changed to compressed air. The oxidation time is 3-5 hours; (10) Catalyst acquisition: Through filtering, washing and drying steps, a water electrolysis catalyst with low Ir loading and high noble metal specific surface area is obtained.

2. The method for preparing the water electrolysis catalyst according to claim 1, characterized in that: Step (1) In RuCl3·hydrate and MnCl2·hydrate, the molar ratio of Ru and Mn ions is 1:1-3.

3. The method for preparing the water electrolysis catalyst according to claim 1, characterized in that: In step (2), the ratio of ethanol to water is 1:1; The molar ratio of carbon black to metal ions is 1:3, and the carbon black is one of Cabot or Ketjen black.

4. The method for preparing the water electrolysis catalyst according to claim 1, characterized in that: In step (2) and step (7), the drying conditions of the magnetic stirrer are: a rotation speed of 600 r / s at 80°C.

5. The method for preparing the water electrolysis catalyst according to claim 1, characterized in that: In step (3), the reduction is carried out at 800°C, the inert atmosphere is H2(5%)-Ar(95%), the reduction time is 2-5h, and the heating and cooling rate is maintained at 2-5°C / min.

6. The method for preparing the water electrolysis catalyst according to claim 1, characterized in that: In step (6), hydrochloric acid is preferably used to adjust the pH value, and the pickling time is 10 hours.

7. The method for preparing the water electrolysis catalyst according to claim 1, characterized in that: In step (8), the reduction is carried out at 900°C, the inert atmosphere is H2(5%)-Ar(95%), the reduction time is 2-5h, and the heating and cooling rate is maintained at 2-5°C / min.

8. A water electrolysis catalyst, characterized in that: Prepared by the preparation method according to any one of claims 1 to 7, wherein the water electrolysis catalyst comprises a substrate and Ir atoms attached to the surface of the substrate; The matrix includes Ru-MnO2.

9. The water electrolysis catalyst according to claim 8, characterized in that: The electrolytic water catalyst structure is divided into three layers: inner, middle and outer; The metal elements in the inner layer of the catalyst include Ru and Mn elements, the metal elements in the middle layer include Ir and Ru elements, and the metal elements in the outer layer include Ir elements.

10. Use of the water electrolysis catalyst as claimed in claim 1 or 2 in electrocatalytic water electrolysis in an electrochemical oxygen evolution reaction.

Citation Information

Patent Citations

  • Ruthenium-based composite oxide material prepared by sol-gel method as well as preparation method and application thereof

    CN111151244A

  • Preparation method of amorphous IrOx / Ru catalyst for PEM water electrolysis hydrogen production

    CN116356361A

  • Preparation method and application of iridium-modified ruthenium-based transition metal doped oxide catalyst

    CN117026271A

  • Manganese-doped ruthenium oxide nano-catalyst as well as preparation method and application thereof

    CN117802528A

  • Rapid solid-phase preparation method of oxide nanowire catalyst with high stress wave level

    CN118147686A